Proceedings of the 14th SIGMORPHON Workshop on Computational Research in Phonetics, Phonology, and Morphology 2016
DOI: 10.18653/v1/w16-2013
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Intra-Word Code-Switching

Abstract: Welcome to the 14th SIGMORPHON Workshop on Computational Research in Phonetics, Phonology, and Morphology. The workshop aims to bring together researchers interested in applying computational techniques to problems in morphology, phonology, and phonetics. Our program this year highlights the ongoing and important interaction between work in computational linguistics and work in theoretical linguistics. We received 23 submissions and accepted 11.The volume of submissions made it necessary to recruit several add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Their language identifier obtained 98.9% precision when classifying texts of four "screen lines" between 19 languages. Nguyen and Cornips (2016) used odds ratio to identify the language of parts of words when identifying between two languages. Odds ratio for language g when compared with language h for morph f i is calculated as in Equation 36.…”
Section: Perplexitymentioning
confidence: 99%
“…Their language identifier obtained 98.9% precision when classifying texts of four "screen lines" between 19 languages. Nguyen and Cornips (2016) used odds ratio to identify the language of parts of words when identifying between two languages. Odds ratio for language g when compared with language h for morph f i is calculated as in Equation 36.…”
Section: Perplexitymentioning
confidence: 99%
“…For Nepali-English, Barman et al (2014) correctly identified some of the mixed words with a combination of linear kernel support vector machines and a k-nearest neighbour approach. The most similar work to ours is Nguyen and Cornips (2016), which focused on detecting intra-word CS for Dutch-Limburgish (Nguyen et al, 2015). The authors utilized Morfessor (Creutz and Lagus, 2002) to segment all words into morphemes and Wikipedia to assign LID probabilities to each morpheme.…”
Section: Related Workmentioning
confidence: 96%
“…Notably, Solorio and Liu (2008) trained classifiers to predict code-switching points in Spanish and English, using different learning algorithms and transcriptions of code-switched discourse, while Nguyen and Dogruöz (2013) focused on wordlevel language identification (in Dutch-Turkish news commentary). Nguyen and Cornips (2016) describe work on analyzing and detecting intra-word codemixing by first segmenting words into smaller units and later identifying words composed of sequences of subunits associated with different languages in tweets (posts on the Twitter social-media site).…”
Section: Introductionmentioning
confidence: 99%